Pemilihan Presiden dan Wakil Presiden Berdasarkan Sistem Presidensial - Imeldah, Imeldah; Nurulaini, Asyifa (Hutanasyah : Jurnal Hukum Tata Negara, 2024)
This academic publication extensively explores the procedures for electing the president and vice president within a presidential system. It analyzes the mechanisms, regulatory structure, and influential factors that determine the selection of these crucial figures. The study provides nuanced insights into how these elections operate uniquely within the context of a presidential system. Targeted at scholars and policymakers, the research contributes valuable information, enhancing our understanding of the distinctive electoral dynamics in systems where the president and vice president undergo separate elections.